2004
DOI: 10.1021/bm0498427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hyaluronan from Different Sources:  Streptococcus zooepidemicus, Rooster Comb, Bovine Vitreous, and Human Umbilical Cord

Abstract: Sodium hyaluronate (HA) is widely distributed in extracellular matrixes and can play a role in orchestrating cell function. Consequently, many investigators have looked at the effect of exogenous HA on cell behavior in vitro. HA can be isolated from several sources (e.g., bacterial, rooster comb, umbilical cord) and therefore can possess diverse impurities. This current study compares the measured impurities and the differences in biological activity between HA preparations from these sources. It was demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 15 publications
2
74
0
Order By: Relevance
“…Importantly, these findings show that BVG has the ability to regenerate the function of serum-starved HDFs. This regeneration occurs because BVG contains high levels of HA (Shiedlin et al 2004). Indeed, previous a study showed that HA could enhance fibroblast extracellular structural mechanical supports, change fibroblast cellular morphologies, re-expose of hidden TGF-β1 receptor and ameliorate the TGF-β1 signaling pathway in procollagen synthesis (Quan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these findings show that BVG has the ability to regenerate the function of serum-starved HDFs. This regeneration occurs because BVG contains high levels of HA (Shiedlin et al 2004). Indeed, previous a study showed that HA could enhance fibroblast extracellular structural mechanical supports, change fibroblast cellular morphologies, re-expose of hidden TGF-β1 receptor and ameliorate the TGF-β1 signaling pathway in procollagen synthesis (Quan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these macromolecules also exhibit little significant quantitative variation among different mammals (Theocharis et al 2008), although bovine vitreous gel contains higher hyaluronic acid levels than other sources, such as Streptococcus zooepidemicus or rooster comb (Shiedlin et al 2004). Additionally, bovine vitreous gel can be obtained from bovine eye-balls, which are found readily from slaughterhouse waste.…”
mentioning
confidence: 99%
“…Hence, there is a strong interest in optimizing HA production processes to obtain products that fulfill high quality standards and are characterized by great yield and accessible costs. Both the source and the purification process concur to determine the characteristics of the produced HA in terms of purity, MW, yield and cost [124,125]. Therefore, producing high quality HA with high yield and less costly methods represents one of the biggest challenges in the field of hyaluronan applied research.…”
Section: Industrial Production Of Hamentioning
confidence: 99%
“…The first production process applied at an industrial scale consisted in HA extraction from animal sources, such as bovine vitreous and rooster combs [46,49,124]. Despite the extraction protocols were improved over the years, this methodology was always hampered by several technical limitations which led to the production of highly polydispersed HA (MW ≥ 10 6 Da) with low yield [1,46].…”
Section: Industrial Production Of Hamentioning
confidence: 99%
See 1 more Smart Citation